Effect of Silibinin in Lowering the Intraocular Pressure in Normotensive Rabbits: Interaction with Pilocarpine and Cyclopentolate - Saad A. Hussain; Haider M. Mohammed; Munaf H. Abdulrazzaq; Ahmed T. Numan (College of Pharmacy University of Baghdad, 2017)
Previous data indicated the effectiveness of silibinin as intraocular pressure (IOP) - lowering agent.  The present study was performed to evaluate the interaction of silibinin with pilocarpine or cyclopentolate in lowering IOP in normotensive rabbits. The effects of topically instilled silibinin hemisuccinate solution (0.75%) alone or adjunctly combined with 2% pilocarpine or 1% cyclopentolate on the IOP of normotensive rabbits were evaluated using indentation tonometry. The results showed that 0.75% solution of silibinin was found more potent than pilocarpine (2% drops) in lowering IOP of normotensive rabbits, while their combination results in longer duration of action. Moreover, the elevated IOP values produced by cyclopentolate (1%drops) were decreased by silibinin, while prior instillation of cyclopentolate did not interfere with the IOP-lowering effect of silibinin. In conclusion Silibinin lowers IOP in normotensive rabbits more than pilocarpine, and their combination elongates the duration of the IOP-lowering effect. This might be due to interference with aqueous humor formation as a possible mechanism. In addition, cyclopentolate did not significantly alter the effect of silibinin on IOP. Key words: silibinin, IOP, pilocarpine, cyclopentolate